2016
DOI: 10.1053/j.gastro.2016.02.073
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Intestinal Microbiome and Alcoholic and Nonalcoholic Liver Diseases: Causes or Effects?

Abstract: The prevalence of fatty liver diseases is increasing rapidly worldwide; after treatment of hepatitis C virus infection becomes more widespread, fatty liver diseases are likely to become most prevalent liver disorders. Although fatty liver diseases are associated with alcohol, obesity, and the metabolic syndrome, their mechanisms of pathogenesis are not clear. Development and progression of fatty liver, alcoholic, and non-alcoholic liver disease (ALD) all appear to be influenced by the composition of the microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 94 publications
(97 reference statements)
4
68
0
3
Order By: Relevance
“…(Chen et al, 2016) Therefore, changes in gut microbiome have been linked to NAFLD, and NASH. (Betrapally et al, 2016; Henao-Mejia et al, 2012)…”
Section: Introductionmentioning
confidence: 99%
“…(Chen et al, 2016) Therefore, changes in gut microbiome have been linked to NAFLD, and NASH. (Betrapally et al, 2016; Henao-Mejia et al, 2012)…”
Section: Introductionmentioning
confidence: 99%
“…Compositional changes in gut microbiota have been proposed to mechanistically contribute to the progression of NAFLD . A higher proportion of Gram‐negative bacterial species in the gut microbiome has been reported in NAFLD and significant changes in the gut microbiome have been linked to NAFLD, NASH and NASH‐related liver fibrosis . We report significant correlation between the abundance of several bacterial species in the gut microbiome and the circulating level of 3‐(4‐hydroxyphenyl)lactacte, including bacterial species associated with advanced fibrosis in a previous study .…”
Section: Discussionmentioning
confidence: 99%
“…The most recent study found the global prevalence of NAFLD was 25% [3]. Individuals with components of metabolic syndrome (MS), such as obesity, insulin resistance, and hyperlipidemia, have an increased risk of developing NAFLD, as positive correlations have been noticed between NAFLD and components of MS [2, 46]. NAFLD is closely related to obesity; however, 5–8% of nonobese (lean) subjects also develop NAFLD [7].…”
Section: Introductionmentioning
confidence: 99%